Economy, Finance and Business in Southeastern and Central Europe Proceedings of the 8th International Conference on the Economies of the Balkan and Eastern European Countries in the Changing World (EBEEC) in Split, Croatia, 2016 (Cham : Springer International Publishing, 2018)
This volume comprises papers presented at the 8th international conference "The Economies of the Balkan and Eastern European Countries in the Changing World" (EBEEC) held in Split, Croatia in 2016. The papers cover a wide range of current issues relevant for the whole of Eastern Europe, such as European integration, economic growth, labour markets, education and tourism. Written by experienced researchers in the field of economic challenges for Eastern Europe, the papers not only analyse recent problems, but also offer policies to resolve them. Furthermore, they offer insights into the theoretical and empirical foundations of the economic processes described. The proceedings of the conference appeals to all those interested in the further economic development of the Balkan and Eastern European countries.
The end of the EURO -- The effects of alternative currencies to national economies: the European experience -- The role of FDI in increasing employment for South-Eastern Europe countries -- Trends in the Balkans and Eurasia under globalization - geostrategic analysis -- The impact of Scandinavian inward foreign direct investment on the Baltic states -- Troika's economic adjustment programmes for Greece: why they fail systematically?- trading volumes of free zones in turkey and evaluation of their contribution to international business -- Advantages and disadvantages of the membership of the Republic of Serbia in the European union -- Greek crisis and its spillovers in South-Eastern Europe -- Failure factors of the economic adjustment programme for Greece -- Eliminating barriers and new challenges in the European labour market -- The internatinalization process of small and medium enterprises: case of Albania -- Global economic governance: between a new compromise or integration -- Export performance of South Eeastern European countries -- Towards competitive dynamics view on oil companies in the south east Europe: analysis of industrial concentration -- Macro and micro innovativeness of the western Balkan countries -- Application of renewable energy sources in Hungary in the South-Transdanubian region -- Making street lighting ESCO projects work in practice -- Fiscal consolidation - impact on labor market outcomes -- Symptoms of burnout in the workplace: comparison between the older and younger employees in Slovenian companies -- Workers in a poultry cooperative: a study on their job satisfaction -- Employee performance, working time and tiredness in creative R&D jobs: employee survey from Estonia -- Analysis of predictors in bankruptcy prediction models for Slovak companies -- Analysis of assets in balance sheet of construction company -- Sand in my eyes fled effect: an evidence from Saudi Arabia -- Financially constrained firms: the impact of managerial optimism and corporate investment on inefficiencies leading to low market valuation - the case of Greece -- Conceptual model of outcomes of perceived fair insurance services -- Corruption and tax compliance of Greek SMEs -- The correlation between four input indicators and six demographic and output indicators within the east European health care systems -- IAS for SMEs adoption: evidence from the regions of Kavala and Serres, Greece -- Accounting system in Croatian public healthcare sector: current state and improvement perspectives -- The comparison of the public sector accounting of Croatia and Bosnia and Herzegovina.-Institutional voids and the role of NGOs in filling voids: the case of Gimdes -- The impact of the external environment on the functioning of SMEs - results of own studies -- The barriers for the development of the social cooperative enterprises in Greece -- Corporate governance in a post-transition period: a case of Slovenia -- Tourism and ecologically sensitive areas: the case of the prefecture of Preveza from citizens' point of view -- The analysis of tourism and economic growth relationship in central and eastern European countries -- Monitoring the impacts of corporate activities on environment in tourism and communicating through corporate reports -- Wine tourism development in northern Greece: evidence from Ktima Gerovassiliou -- Selected aspects of human resource management supporting and limiting organizational learning -- The agile revolution in software engineering -- Metaeconomic approaches in global management -- Defining decision making process for student learning support system -- Knowledge transfer and trust among partners: The case of Greek IJVS -- Examination of two companies' liability management -- Marketing expansion strategies in multinational marketing : the role of e-business -- Is marketing research still necessary in the digital world?- conspicuous consumption in relation to self-esteem, self-image and social status: an empirical study -- Measuring citizens satisfaction from public sector organisations in Greece: the case of the regional district of Xanthi -- Social marketing in public sector - the case of municipality in Croatia -- Decision support system for marketing metrics -- Designing an intelligent digital signage system for business marketing -- Assesing the cost information usage in higher education institutions - case study in Croatia and Bosnia and Herzegovina -- Research areas in big data analytics studies -- Students' perceptions of quality and satisfaction on the higher education -- Greek tertiary education system evaluation in respect of quality assurance dimensions according to Malcom Baldrige performance excellence model -- Learning styles and preferences for different types of courses and teaching of Croatian students of business -- Comparative analysis of internal reporting at higher education institutions of Croatia and Bosnia and Herzegovina -- M&A in ICT sector: methodology of parameters analysis -- Web based it firm evaluation: which one is the right solution?- Digital divide in Greece- a quantitative examination of internet non-use.
Economics and Finance
text file PDF
Keywords: Europe-Economic conditions; Macroeconomics; European Economic Community literature; Economic growth; Finance, Public; Industries